2014
DOI: 10.3928/21650799-20140305-05
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Behavior Among Nurses in Rural Greece

Abstract: Evidence suggests that rural health care providers may be at increased risk for tobacco addiction. Few researchers have studied the habitual use of tobacco in rural Greece and no published studies have examined sustained tobacco use by nurses working in these areas or their knowledge and attitudes toward smoking cessation. To explore the above, the authors conducted a questionnaire-based study in 40 health centers in rural mainland and island Greece. Two hundred twenty nurses were surveyed (65% response rate).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Pakistan'da 180 sağlık çalışanı ile yapılan çalışmada sigara içme sıklığı %29,4, Ukrayna'da yapılan bir çalışmada ise sigara içme sıklığı pediatristlerde %32,5, aile hekimlerinde %37,5 ve intörnlerde %50'dir [14][15]. Yunanistan'da 220 hemşire ile yapılan bir çalışmada ise sigara içme sıklığı %32'dir [16]. Ulusal ve uluslararası sağlık çalışanlarının sigara içme sıklığını ölçmek amacı ile yapılan çalışmalardaki bu çeşitliliğin nedenleri arasında, katılımcıların sayısı ve demografik özelliklerindeki farklılıklar ve çalışmanın yapıldığı ortam farklılıkları sayılabilir.…”
Section: Discussionunclassified
“…Pakistan'da 180 sağlık çalışanı ile yapılan çalışmada sigara içme sıklığı %29,4, Ukrayna'da yapılan bir çalışmada ise sigara içme sıklığı pediatristlerde %32,5, aile hekimlerinde %37,5 ve intörnlerde %50'dir [14][15]. Yunanistan'da 220 hemşire ile yapılan bir çalışmada ise sigara içme sıklığı %32'dir [16]. Ulusal ve uluslararası sağlık çalışanlarının sigara içme sıklığını ölçmek amacı ile yapılan çalışmalardaki bu çeşitliliğin nedenleri arasında, katılımcıların sayısı ve demografik özelliklerindeki farklılıklar ve çalışmanın yapıldığı ortam farklılıkları sayılabilir.…”
Section: Discussionunclassified
“…In Croatia, Juranic et al 28 reported that 35.1% of healthcare personnel were habitual smokers whilst Azuri and Nashef 29 , in Israel, with a sample of 302 physicians, observed a prevalence of 13.5%. Stamatopoulou et al 30 , in a study undertaken in 40 health centers in rural mainland and island Greece, reported that 32% of the nurse respondents were smokers. Data from a study carried out by Huddlestone et al 31 in the UK with a sample of 171 PHC personnel revealed that 11% consumed tobacco.…”
Section: Comparison With Other Countriesmentioning
confidence: 99%